Quality of work, economic crisis, and temporary employment. Issue 1 (29th October 2019) - Bartoll, Xavier; Ramos, Raul
Abstract : Purpose: The purpose of this paper is to analyse the association between the type of contract (temporary vs permanent) and the quality of work and its different dimensions before and after the economic crisis among Spanish employees. Design/methodology/approach: Structural equations techniques are used to analyse the association between the type of contract and the work quality and its different dimensions before and after the crisis. Data are drawn from the 2006/2007 and 2009/2010 waves of the Encuesta de Calidad de Vida en el Trabajo. Findings: The results show that in the two considered periods there are no differences in quality of work among male involuntary temporary workers and those with permanent contracts. However, there is an adverse widening gap across all dimensions of work quality for women in involuntary temporary employment during the economic crisis. There is also a shift among men and women in involuntary temporary employment from valuing intrinsic job quality dimension in the pre-crisis period to valuing more the work environment dimension during the crisis period. Research limitations/implications: The analysis is limited by the continuity of variables across years and the high proportion of missing values in some variables. The obtained results cannot be interpreted in terms of causality. Originality/value: This is the first study to consider whether the deterioration in the Spanish labour market during the crisis has affected the relationship between the type of contract and the different dimensions of the quality of work.